Removal of a Third Molar and Dentigerous Cyst from the Orbital Floor in Maxillary Sinus: A Case Report - Dündar, Serkan; Karlıdag, Turgut; Keles, Erol (My University, 2020)
Dentigerous cysts are odontogenic lesions associated with the crown of permanent teeth. Theselesions are nonmalignant. Dentigerous cysts, which surround impacted teeth, can cause teeth tobecome ectopic. In the maxilla, impacted teeth associated with dentigerous cysts are oftendisplaced towards the maxillary sinus cavities. These lesions can be successfully treated withCaldwell-Luc surgery and/or endoscopic sinus surgery. We report a case of a dentigerous cyst inthe maxillary sinus associated with an ectopic third molar and its treatment.
Keywords: Diş Hekimliği; Cerrahi